Application Of Bacillus Sphaericus Upmb10 For Growth Enhancement Of Banana (Musa Spp. Var. Berangan) And Its Effect On Fusarium Wilt - Ibrahim, Illani Zuraihah (2008)

(untitled)
A locally isolated strain Bacillus sphaericus UPMB10, categorized as plant growth promoting rhizobacteria (PGPR), was reported to have beneficial effects in stimulating growth and yield of many agricultural crops. This study explores the indirect mechanism of B. sphaericus UPMB10 that would support the hypothesis that this PGPR could act as a biocontrol agent. Through invitro study, B. sphaericus UPMB10 was observed to inhibit the growth of Fusarium oxysporum f.sp cubense race 4 (FOCR4) mycelium by 70% in culture medium. Malformation of the fungal hyphae by vacuole formation, swelling and thickening of the hyphal strands occurred with the presence of B. sphaericus UPMB10. In addition, B. sphaericus UPMB10 showed positive results in the tests for production of cell wall-degrading enzymes and phosphate solubilizing activity by producing clear zones or halos. It can also produce a plant growth regulating hormone, indole acetic acid (IAA). An initial glasshouse study showed that inoculation with B. sphaerius UPMB10 increased plant growth up to 30% in plant height and increased nutrient uptake namely for N, P, K, and Ca, and also reduced the disease severity through visual symptoms and vascular discoloration of the corm. In the last glasshouse experiment, the appearance of the disease incidence was observed. All of the treatments with FOCR4 application were infected by FOCR4 including those treated with B. sphaericus UPMB10. Significantly, the infection occurred at the late stage of the experiment indicating that B. sphaericus UPMB10 could delay the infection process. Solid inoculum inoculation with B. sphaericus UPMB10 showed a delayed onset of symptoms, lower percentage in disease incidence and epidemic rate. As liquid and solid substrate were selected for evaluation against the disease in the glasshouse, it showed that soil application of B. sphaericus UPMB10 with solid inoculum provided the best suppression of Fusarium wilt of banana. In this study, an inoculum dose of 100 g of solid formulation per plant was optimum, because it suppressed the disease to the same extent as higher doses of the antagonist. This showed B. sphaericus UPMB10 has a high potential for its use as a plant growth enhancer and biocontrol agent in the disease management of Fusarium wilt in bananas.